Functional assessment of cerebral artery stenosis: A pilot study based on computational fluid dynamics. Issue 7 (July 2017) - Liu, Jia; Yan, Zhengzheng; Pu, Yuehua; Shiu, Wen-Shin; Wu, Jianhuang; Chen, Rongliang; Leng, Xinyi; Qin, Haiqiang; Liu, Xin; Jia, Baixue; Song, Ligang; Wang, Yilong; et al.
The fractional pressure ratio is introduced to quantitatively assess the hemodynamic significance of severe intracranial stenosis. A computational fluid dynamics-based method is proposed to non-invasively compute the FPRCFD and compared against fractional pressure ratio measured by an invasive technique. Eleven patients with severe intracranial stenosis considered for endovascular intervention were recruited and an invasive procedure was performed to measure the distal and the aortic pressure ( Pd and Pa ). The fractional pressure ratio was calculated asP d / P a . The computed tomography angiography was used to reconstruct three-dimensional (3D) arteries for each patient. Cerebral hemodynamics was then computed for the arteries using a mathematical model governed by Navier–Stokes equations and with the outflow conditions imposed by a model of distal resistance and compliance. The non-invasiveP d - CFD, P a - CFD, and FPRCFD were then obtained from the computational fluid dynamics calculation using a 16-core parallel computer. The invasive and non-invasive parameters were tested by statistical analysis. For this group of patients, the computational fluid dynamics method achieved comparable results with the invasive measurements. The fractional pressure ratio and FPRCFD are very close and highly correlated, but not linearly proportional, with the percentage of stenosis. The proposed computational fluid dynamics method can potentially be useful in assessing the functional alteration of cerebral stenosis.